The role of interbank relationships and liquidity needs - Ben R. Craig; Falko Fecht; Günseli Tümer-Alkan (Deutsche Bundesbank, 2013)
In this paper, we focus on the interconnectedness of banks and the price they pay for liquidity. We assess how the concentration of credit relationships and the position of a bank in the network topology of the system influence the bank's ability to meet its liquidity demand. We use quarterly data of bilateral interbank credit exposures between all German banks from 2000 to 2008 to measure interbank relationships and the network characteristics. We match these data with the bids placed by the individual banks in the European Central Bank's (ECB) weekly repo auctions. The bids measure each bank's willingness to pay for liquidity since they had variable rate tenders with a 'pay-your-bid' price. Controlling for bank characteristics and the daily fulfillment of reserve requirements, we find that banks with a more diversified borrowing structure in the interbank market bid significantly less aggressively and pay a lower price for liquidity in the ECB's main refinancing operations. These findings suggest that incentives to diversify bank liquidity risk dominate the benefits of private information. When the network position of the bank is taken into account, we find that central lenders in the money market bid more aggressively in the auctions.
Keywords: G21; E58; D44; L14; D85; 330; Interbank markets; liquidity; relationship lending; networks